In vitro functional characterization of splicing variants of the APOB gene found in familial hypobetalipoproteinemia - Rabacchi, Claudio; Simone, Maria Luisa; Pisciotta, Livia; Di Leo, Enza; Bocchi, Davide; Pietrangelo, Antonello; D'Addato, Sergio; Bertolini, Stefano; Calandra, Sebastiano; Tarugi, Patrizia (Journal of clinical lipidology, 2019)
Familial hypobetalipoproteinemia type 1 (FHBL-1) is a codominant disorder characterized by greatly reduced plasma levels of total cholesterol, low-density lipoprotein cholesterol, and apolipoprotein B. Rare exonic pathogenic variants of APOB gene (nonsense variants, minute deletions/insertions and nonsynonymous variants) have been frequently reported in subjects with FHBL-1. Also, rare intronic variants of APOB located at intron/exon junctions and assumed to affect splicing have been reported. However, the pathogenicity of most of these intronic variants remains to be established. The objective of this study was the in vitro functional characterization of six splicing variants of APOB gene identified in seven putative FHBL-1 heterozygotes. ApoB minigenes harboring each variant were expressed in COS-1 cells and their transcripts were sequenced. Four novel variants (c.237+1G>A, c.818+5G>A, c.3000-1G>T, and c.3842+1G>A), predicted in silico to obliterate splice site activity, were found to generate abnormal transcripts. The abnormal transcripts were generated by the activation of cryptic splice sites or exon skipping. All these transcripts harbored a premature termination codon and were predicted to encode truncated apoBs devoid of function. The predicted translation products were: i) p.(Lys41Serfs*2) and p.(Val80Ilefs*10) for c.237+1G>A; ii) p.(Asn274*) for c.818+5G>A; iii) p.(Leu1001Alafs*10) for c.3000-1G>T, and iv) p.(Ser1281Argfs*2) for c.3842+1G>A. Two previously annotated rare variants (c.905-15C>G and c.1618-4G>A) with uncertain effect in silico were found to generate only wild-type transcripts. These in vitro minigene expression studies support the assignment of pathogenicity to four novel splice site variants of APOB gene found in FHBL-1. •APOB gene variants may be the cause of familial hypobetalipoproteinemia (FHBL-1).•Six rare APOB intronic variants involving splice sites were found in FHBL-1 subjects.•The functional impact of each variant was assessed in vitro using minigene strategy.•Four variants were found to generate abnormal transcripts encoding truncated apoBs.